Acellular vascular tissues: natural biomaterials for tissue repair and tissue engineering - Schmidt, Christine E.; Baier, Jennie M. (Biomaterials, 2000)
Various research groups around the world are actively investigating cardiovascular prostheses of biological origin. This review article discusses the need for such bioprosthetics and the potential role for natural tissues in cardiovascular applications such as cardiac valves and vascular grafts. Upon implantation, unmodified natural materials are subject to chemical and enzymatic degradation, seriously decreasing the life of the prosthesis. Therefore, methods such as glutaraldehyde and polyepoxide crosslinking treatments and dye-mediated photooxidation have been developed to stabilize the tissue while attempting to maintain its natural mechanical properties. Also, residual cellular components in a bioprosthetic material have been associated with undesired effects, such as calcification and immunological recognition, and thus have been the motivation for various decellularization processes. The effects of these stabilization and decellularization treatments on mechanical, biological and chemical properties of treated tissues have been investigated, specifically with regard to calcification, immunogenicity, and cytotoxicity concerns. Despite significant advances in the area of cardiovascular prostheses, there has yet to be developed a completely biocompatible, long-lasting implant. However, with the recent advent of tissue engineering, the possibility of applying selective cell seeding to naturally derived bioprosthetics moves us closer to a living tissue replacement.